2018
DOI: 10.1021/acs.jpcc.8b00061
|View full text |Cite
|
Sign up to set email alerts
|

In Situ DRIFTS and NAP-XPS Exploration of the Complexity of CO2 Hydrogenation over Size-Controlled Pt Nanoparticles Supported on Mesoporous NiO

Abstract: Infrared Fourier Transform Spectroscopy (DRIFTS). In the case of pure NiO, we found that the surface of the support was mainly covered by elemental Ni under reaction condition, where the Ni/NiO x system is responsible for the high activity of Pt-free catalyst. In the case of Pt/NiO, Pt improves the reduction of NiO x towards metallic Ni. In the case of the 1 % Pt/NiO catalysts, the presence of limited amount of Pt resulted in an optimal quantity of oxidized Pt fraction at 673 K showing the presence of a Pt/PtO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 66 publications
(149 reference statements)
0
42
0
Order By: Relevance
“…On Pd‐supported Al 2 O 3 catalysts, methane formation was dominant, whereas using SiO 2 , MgO and TiO 2 supports CO was the major product . The ratio of Ni:NiO also strongly determines the selectivity of the CO 2 hydrogenation: higher metallic content favors methane formation . All of these findings emphasize the importance of the nature of the metal/support interface.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…On Pd‐supported Al 2 O 3 catalysts, methane formation was dominant, whereas using SiO 2 , MgO and TiO 2 supports CO was the major product . The ratio of Ni:NiO also strongly determines the selectivity of the CO 2 hydrogenation: higher metallic content favors methane formation . All of these findings emphasize the importance of the nature of the metal/support interface.…”
Section: Resultsmentioning
confidence: 94%
“…[37] The ratio of Ni:NiO also strongly determines the selectivity of the CO 2 hydrogenation:h igher metallic content favors methane formation. [29] All of these findings emphasize the importance of the nature of the metal/support interface. The absence of an oxide-like interaction between the metal and BCNT could be the reason for high CO selectivity in the present study.T he BCNT ensures as pherical, site-specific arrangement for the metal where the CO 2 reductive activation may occur.I n the case of Ni/BCNT there is ac hance to build up af avorable Ni/NiO composition at am oderatet emperature where the methane formation is dominant.…”
Section: Catalytic Hydrogenation Of Comentioning
confidence: 96%
“…The Pt NP dispersion on the surface of the H-ZSM-5 supports may depend on the acidic strength of the support: the more acidic is the surface, the less sintering during the reaction maybe expected. However, earlier studies showed that Pt nanoparticles with >5 nm sizes are not showing any sintering under similar reaction conditions (Sápi et al, 2018). It is worth mentioning that the lack of the Brønsted acidic sites over the zeolite supports, the Pt NPs are not stable and consequently might be leading to the formation of their agglomeration over the support.…”
Section: Structural and Textual Propertiesmentioning
confidence: 90%
“…These bands can be attributed to the formation of formate ion (HCOO − ) from the CO 2 + H 2 reaction mixture, and these are assigned to ν a (OCO) and ν s (OCO) vibrations, respectively (Liao et al, 2001;Raskó et al, 2004). When the reaction temperature is increased to 573 K, a new weak peak developed at 1,737 cm −1 which can be tentatively assigned to aldehyde like CO stretch (Novák et al, 2002;Sápi et al, 2018). These bands were present up to 873 K, from 673 K peaks for gas phase CO (2,115 and 2,167 cm −1 ) and methane (3,013 cm −1 ) showed up (not shown here).…”
Section: In-situ Drifts Studies Of the Catalysts Under Reaction Condimentioning
confidence: 99%
See 1 more Smart Citation